EDUKASI NUTRITION GOES TO SCHOOL PADA GURU SEKOLAH MENENGAH PERTAMA DI KABUPATEN TANJUNG JABUNG TIMUR - Guspianto; Ismi Nurwaqiah Ibnu; Puspita Sari (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2023)
Teachers as educators in schools and substitutes for parents have a very important role in providing education and exemplary clean and healthy living behaviors for students, as mentors in learning, as well as mentors and motivators. This Community Service (PkM) aims to provide education to junior high school teachers about nutritional literacy, namely nutrition goes to school as one of the efforts to intervene in nutrition in the school setting. The PkM location is Tanjung Jabung Timur 21 Public Middle School with a target of 25 teachers. Education is provided through the NGTS module directly followed by pre-test and post-test, and each teacher is required to apply the material taught to students within 1 month. The results of the pre-test and post-test analysis revealed that there was an increase in teacher knowledge about the NGTS educational model. This community service activity has been published in online mass media, namely the Jambi Tribune. It is hoped that the school will increase the capacity and capability of teachers in fostering efforts to improve the health and nutrition of students through learning and motivation, and continue to create a work environment that supports clean and healthy living behaviors.